الإشاريــات الشخصيــة فـي ســـــــورة طه - شهلة سعودي; صبرينة صالحي (University of Eloued جامعة الوادي, 2025)
الملخص: يعد الخطاب القرآني مدونة مناسبة لتطبيق الآليات التأويلية التداولية في أغلب مباحثها؛ نظرا لحاجته ربط المعارف اللغوية بالمعارف السياقية في فهم معانيه، ومن بين هذه الآليات ذات الأهمية البالغة في ذلك "الإشاريات "، هذه الأخيرة بدورها تنقسم إلى خمسة أنواع؛ من بينها الإشاريات الشخصية، التي خصصناها بالدراسة في موضوعنا هذا، عليه جاءت صياغة العنوان كالآتي: الإشاريات الشخصية في سورة طه. وبعد النظر في فحوى الإشاريات في شقها النظري قمنا بالنظر فيها من خلال السورة؛ بهدف معرفة دور/فاعلية الإشاريات الشخصية في بناء الخطاب القرآني بصفة عامة وسورة طه بصورة خاصة. ومن خلال ذلك توصلنا إلى مجموعة من النتائج. -أن التداولية هي نظرية لسانية وجدت صداها في المدة الأخيرة؛ إذ استطاعت أن تتخذ لنفسها طريقا بوصفها تخصصا لسانيا له موضوع خاص مستقل يدرس كيفية استخدام الناس للغة في صلب الخطاب. -تعدّ الإشاريات من أهم الظواهر التداولية التي لا يمكن فصلها عن السياق؛ إذ تسهم في تحديد هوية المشاركين في الخطاب والعلاقة بينهم؛ ممّا يؤدي ذلك إلى تحديد أغراض ومقاصد المتكلم، وهذا ما وصلنا إليه من خلال ما جاء في النظري ثم ما وصلنا إليه في التطبيق. -وقد استنتجنا بعد دراسة سورة طه أنّ الإشاريات الشخصية وظفت بصورة كثيرة لتخدم مقاصد وأغراض السورة. -كما لاحظنا أن النّوْع الإِشاريُّ الطاغي من خلال النماذج المدروسة، هو: الضمائر وخاصة ضمائر المتكلم والمفرد والجمع عند الحديث الإلاهي مما دل على عظمة وقدرة الله -كما أن تكرار ضمير المخاطب في الحوار بين الله وموسى ساعد على تأكيد العلاقة التوجيهية والتأثير في دعوته، ثُم يلِيهِ النداء، ثم الأسماء الموصولة، ثُم أسماء الإِشارَة. -ومِن خلال دراستنا لسورة "طه" ورصدنا للأغراض المتنوّعة الموجودة في الحوارات، تبين أنَ الأغراض الطاغية تمثلت في غرضين هما: تعظيم القدرة الإلهية، والاستئناس، وبالجمع بينهما حملا معنى التوجيه والدعوة. Résumé :فرنسية أو انجلزية Quranic discourse is a suitable corpus for applying pragmatic hermeneutical mechanisms in most of its discussions, given its need to link linguistic knowledge with contextual knowledge in understanding its meanings. Among these mechanisms, which are of paramount importance in this regard, are "denotations." These, in turn, are divided into five types, including personal denotations, which we have devoted the study of in this topic. Therefore, the title is formulated as follows: Personal Denotations in Surat Taha. -After examining the theoretical content of denotations, we examined them through the surah, aiming to understand the role/effectiveness of personal denotations in constructing Quranic discourse in general and Surat Taha in particular. Through this, we arrived at a set of conclusions. -Pragmatics is a linguistic theory that has gained traction in recent times, having established itself as a linguistic specialty with a distinct subject area that studies how people use language within discourse. -Denotations are among the most important pragmatic phenomena that cannot be separated from context. It contributes to defining the identity of the participants in the discourse and the relationship between them, which leads to defining the speaker's purposes and intentions. This is what we have arrived at through our theoretical and practical findings. -After studying Surah Taha, we concluded that personal references were employed extensively to serve the surah's purposes and intentions. -We also noted that the predominant reference type in the studied models is pronouns, especially the first-person, singular, and plural pronouns in divine discourse, which demonstrates God's greatness and power. -The repetition of the second-person pronoun in the dialogue between God and Moses also helps to confirm the directive relationship and influence his call. This is followed by the vocative, then the relative pronouns, then the demonstrative pronouns. Through our study of Surah Taha and our observation of the various purposes present in the dialogues, it became clear that the predominant purposes were two: glorifying divine power and seeking comfort. Combined, these two aims conveyed the meaning of guidance and invitation.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: التداولية، الإشاريات الشخصية، التأويل، القصد; pragmatics; personal allusions; interpretation; intention